The Politics of Legal Reform of the Judicial System in Ensuring Access to Justice for Society - Martareda Eda; Sisilia Eda (Perkara : Jurnal Ilmu Hukum dan Politik, 2025)
This study examines the politics of legal reform in the judicial system and the role of that reform in ensuring access to justice. Judicial reform has largely emphasized institutional efficiency and regulatory modernization, often overlooking the political-legal dynamics that shape access to justice. This research aims to analyze how legal reform policies are formulated through political legal choices and their implications for equitable access to justice. Using a normative legal research method with a qualitative analytical-descriptive approach, this study draws on statutory, conceptual, and policy analyses supported by primary, secondary, and tertiary legal materials. The findings indicate that judicial reform reflects underlying political and legal orientations that influence policy priorities and outcomes. Although reforms have strengthened institutional and regulatory frameworks, their impact on substantive access to justice remains uneven due to a predominant normative focus and limited responsiveness to social realities. This study highlights the importance of integrating access to justice into judicial reform agendas and emphasizes the need for stronger political and legal commitment to inclusive, justice-oriented legal development.